Biosurfactant-driven synergic roles to accelerate biofilm formation in an anaerobic moving bed biofilm reactor (MBBR): A comprehensive analysis on meso and micro scale. (1st November 2022) - Song, Zi; Liao, Runfeng; Wang, Mingming; Zhang, Jianjun; Dong, Zijun; Wen, Zheng; Dong, Wenyi; Sun, Feiyun
Abstract: Biofilm formation is a complex and time-consuming process, especially the attachment and growth of anaerobic biofilm, which fundamentally determines the start-up of biofilm reactor. In this study, biosurfactant, rhamnolipid, was introduced into an anaerobic moving bed biofilm reactor (AnMBBR) to promote its start-up, and the results showed that AnMBBR with rhamnolipid (RMBBR) could be successfully started within 25 days. Compared to the control AnMBBR without rhamnolipid, the start-up time was shortened by about half, the attached biomass on biocarriers was increased to 1.5 times, and the pollutants removal efficiencies were all greatly improved in the start-up phase, especially NO3 − increased from 86.76 ± 1.04% to 96.93 ± 0.73%, and then these gaps were reduced in the steady-state phase. Under the action of rhamnolipid, the adhesion force of the biofilm increased from 18.9 nN to 27.4 nN eventually, and the interfacial energy between biofilm and biocarriers was transformed from repulsion (6200 KT) to weak attraction (−100 KT) by the evaluation of the extended Derjaguin–Landau–Verwey–Overbeek theory, which significantly promoted the initial attachment of biofilm. The increased metabolic activity, key enzyme activity, extracellular polymeric substances (EPS) and quorum sensing behaviors evidenced that rhamnolipid stimulated microbial internal activities and then regulated biofilm growth process. Moreover, rhamnolipid also significantly enhanced the abundance of functional bacteria in terms of metabolism or quorum sensing, including Thauera, Methylomonas, Desulfomicrobium, Azoarcus, Leptonema . Rhamnolipid would also stimulate the expression of genes that related to membrane transport, biofilm formation and nitrogen metabolism. This work provided a promising strategy for the rapid start-up of anaerobic biofilm reactor. Graphical abstract: Image 1 Highlights: Rhamnolipid accelerated the start-up of anaerobic MBBR by promoting biofilm formation. Multiple regulatory mechanisms of rhamnolipid on biofilm formation were first proposed. Rhamnolipid changed functional and structural characteristics of cell membrane. The interfacial energy between biofilm and biocarriers was reduced by rhamnolipid.